Understanding the Sukuk Market in Malaysia : Corporate Perspective - Mahmud, Khairul Emran (2011)
The emergence of sukuk has created wide interest among corporate as an alternative funding instrument. It also provides Shariah conscious entities, either fund raiser or fund provider, a viable instrument to either utilise or invest. Malaysia is at the forefront of global sukuk issuance and has remained the largest sukuk market globally. The success of Malaysia is underpinned by its supportive policies and innovation leading to high corporate participation in the market.